The challenges of academic retention in Distance Learning: identification and analysis of Critical Success Factors (Research, Society and Development, 2022)
Distance Learning (DL) grows significantly in Brazil, however, it faces challenges in its management, such as, for example, guaranteeing academic retention and avoiding student dropout. In this sense, mapping and knowing the Critical Success Factors (CSF) related to the modality allows managers to prioritize actions that guarantee the competitiveness and sustainability of this teaching model. This study aimed to identify the CSF that affect the permanence in a course of Technology in Human Resources Management, Distance Learning modality, offered by a university center located in the city of Valença-RJ. It is a field research, descriptive-exploratory, with a qualitative approach and basic nature. Data collection was carried out through questionnaires and the analysis was carried out with the aid of descriptive statistics. Based on the results, it was found that teachers/tutors, study environment, time availability, motivation, discipline, teaching material, proposed activities, course duration, technological skills, family incentives and health conditions represented CSF that facilitate the permanence on the course. It is expected that this study will contribute to the development of strategies aimed at student retention, which will reflect on the institution’s financial budget and on the municipality’s social development.